Research Article of the Poem Lady Lazarus A Study to Analyze Lady Lazarus through the Feminist Criticism Lens - Zsa Zsa Adelia Attaqiyyah; Muhammad Daffa Al Rasyid; Faldy Alhafiz Hutabarat; Habibi Fajar Simanjuntak; Piqri; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the poem Lady Lazarus by Sylvia Plath using a feminist critical perspective. The main focus is on how the representation of the female body, trauma, and patriarchal power relations appear in the poem. The poem portrays a woman who repeatedly â€œresurrectsâ€ from death, symbolizing resistance against social control and objectification. Therefore, this study seeks to reveal how the female voice is constructed as a form of resistance against male dominance. The method used is a qualitative approach with textual analysis. The data consists of the poem itself, which is examined using feminist criticism, particularly concepts related to the female body, objectification, and patriarchal power. The analysis is conducted by identifying symbols, metaphors, and diction that reflect womenâ€™s experiences and their resistance to oppressive social structures. The results show that Lady Lazarus represents a woman who is aware of her oppression. The speaker refuses to remain a passive object and instead reclaims her body and identity through repeated acts of â€œresurrection.â€ In conclusion, the poem not only depicts female suffering but also asserts female strength and agency in resisting patriarchal systems. Keywords: feminist criticism, female body, patriarchy, resistance, Sylvia Plath